Factors Affecting the Composite Stock Price Index during Covid-19 Pandemic Crisis - Hidayat, Ariodillah; Liliana, Liliana; Andaiyani, Sri (Universitas Negeri Semarang, 2021)
This paper aims to analyze factors affecting the Composite Stock Price Index (IHSG) on the Jakarta Stock Exchange (IDX) during the Pademi Corona Crisis. This study uses the multiple linear regression analysis technique where the variable number of confirmed Covid-19 cases in the world, the number of confirmed Covid-19 cases in Indonesia, the Rupiah exchange rate per 1 US dollar,Â and the world crude oil price are used as independent variables (X) and the IHSG as the dependent variable (Y), the data used in this study are weekly time series data from the period December 2019 to September 2020. Based on the results of variable regression between the IHSG, Exchange Rates, Oil Prices, cases of COVID-19 in Indonesia and COVID-19 World, It is concluded that collectively the independent variables have a significant effect on the IHSG. Partially, Oil Prices, COVID-19 cases in Indonesia and COVID-19 cases in the world have a significant effect on the IHSG. Meanwhile, the exchange rate has no significant effect on the IHSG.